Catch-up growth and metabolic outcomes in adolescents born preterm. Issue 11 (10th June 2016) - Embleton, Nicholas D; Korada, Murthy; Wood, Claire L; Pearce, Mark S; Swamy, Ravi; Cheetham, Timothy D
Abstract : Background: Accelerated infant weight gain in individuals born full term is linked to cardiovascular risk in adulthood, but data in those born preterm are inconsistent. Objective: To investigate the association between weight gain in infancy and childhood with later markers of the metabolic syndrome in adolescents who were born preterm. Study design: Longitudinal cohort study. Setting: Children born preterm with regular assessments of infant growth had auxology, body composition (dual X-ray absorptiometry), blood pressure, insulin sensitivity and lipid profile determined in adolescence. Results: We reviewed 153 children (mean gestation 30.8 weeks, median birth weight 1365 g) of whom 102 consented to venepuncture at a median age of 11.5 years. Adolescent height and weight standard deviation scores (SDS) were similar to population averages (0.01±0.92 and 0.3±1.2, respectively) and did not differ between infants when grouped according to degree of catch-up in weight gain in the immediate postdischarge period to 12 weeks of age. There were no significant associations between infant weight gain (change in weight SDS adjusted for length) and later metabolic outcome. However, there were strong associations between more rapid childhood weight gain (after 1 year of age) and subsequent body composition (higher fat mass %, fat mass index and waist circumference) and metabolic markers (higher fasting insulin, blood pressure and lower insulin sensitivity). Conclusions: The association of rapid weight gain on health is time critical in those born preterm; in early infancy, this does not impact on metabolic status in adolescence, in contrast to rapid weight gain in childhood, which should be discouraged. However, given the critical importance of brain growth in the neonatal period and infancy, further research is needed before strategies that discourage infant weight gain or catch-up can be recommended for infants born preterm.